PSII-11 The cellular immune system in Bos indicus cattle is not altered by short-duration transport. (7th December 2018) - Wagner, B; Parker, A
Abstract: Prolonged or extreme activation of the hypothalamo-pituitary-adrenal (HPA) axis can impact immune status, increasing animal susceptibility to common diseases such as shipping fever. Changes in the physiological, psychological, and behavioral manifestations of stress have been observed in association with increases in circulating oxytocin. Providing oxytocin intranasally has been shown to attenuate stressor-induced HPA axis activation in several species. The present study aimed to investigate the effect of intranasal oxytocin supplementation on stressor-induced activation of the HPA axis and immune status in recently weaned cattle. Thirty, Bos indicus steers were weighed and randomly allocated to one of three treatment groups: 1 ) Saline, not transported (S-NT; 0.015mL/kg bodyweight 0.9% isotonic saline; n = 10); 2 ) Saline, 6 h road transport (S-T; 0.015mL/kg BW 0.9% isotonic saline; n = 10); and 3 ) Oxytocin, 6 h road transport (OXT-T, 0.3 IU/kg BW oxytocin; n = 10). Oxytocin and saline were administered intranasally. Blood samples and bodyweights were taken at hours 0, 6, 48, and 72, relative to the start of transportation. We hypothesized that cattle treated intranasally with oxytocin would have an attenuated transportation-induced activation of the HPA axis compared with transported and non-transported cattle given intranasal saline, ultimately sustaining immune function. No differences ( P > 0.10) between treatment groups were detected for plasma cortisol, glucose, or lactate concentrations. Neutrophil and eosinophil counts were greater and lesser ( P ≤ 0.02), respectively, directly following 6 h road transportation. Under the conditions of the present study, neither oxytocin nor 6 h road transportation affected measured indicators of HPA axis activation. Only mild, short-term effects of 6 h road transportation on immune status were detected and the effects of intranasal oxytocin supplementation in cattle are still unclear; finding an appropriate stress model will be crucial for moving forward with intranasal oxytocin research in cattle.